Performance Management Systems and Employee Performance in Banking: Examining the Mediating Role of Performance Management System Effectiveness - Rendy Martiandita; Wa Ode Zusnita Muizu (GoAcademica Research & Publishing, 2026)
Performance management systems aim to align individual contributions with organizational objectives through goal setting, monitoring, coaching, feedback, evaluation, and development. However, formal implementation does not necessarily ensure system effectiveness or improved employee performance. This study examines the relationships among performance management system implementation, performance management system effectiveness, and employee performance among Consumer Relationship Officers at a bank. A quantitative approach involved 174 Consumer Relationship Officers as respondents and 63 Business Managers as performance evaluators. The officers assessed performance management system implementation and system effectiveness, while the managers independently evaluated employee performance. The proposed relationships were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Performance management system implementation comprised six stages: prerequisites, performance planning, performance execution, performance assessment, performance review, and performance renewal and recontracting. System effectiveness was measured through fairness, goal clarity, feedback, accuracy, and usefulness, while employee performance encompassed task, adaptive, contextual, and counterproductive work behavior. The results show that performance management system implementation positively and significantly affects both system effectiveness and employee performance. System effectiveness also positively and significantly influences employee performance and provides complementary partial mediation between system implementation and employee performance. These findings highlight the importance of moving beyond procedural compliance by ensuring that performance management practices promote fairness, clarity, credible feedback, accurate information, and practical value, supported by managerial evaluation for a more comprehensive assessment of employee performance.